Pharmacokinetics and pulmonary distribution of Draxxin® (tulathromycin) in healthy adult horses. Issue 5 (14th March 2021) - Leventhal, Hannah R.; McKenzie, Harold C.; Estell, Krista; Council‐Troche, McAlister; Davis, Jennifer L.
Abstract: The objective of this study was to determine the pharmacokinetics and tolerability of tulathromycin (Draxxin ® ; 2.5 mg/kg once) after intramuscular (IM), subcutaneous (SC), and slow intravenous (IV) administration to six adult horses. A three‐phase design and 4‐week washout period were used. Drug concentrations in blood and bronchoalveolar lavage (BAL) samples were determined by ultra‐performance liquid chromatography tandem mass spectrometry and pharmacokinetic parameters calculated using noncompartmental analysis. Following SC and IM administration, all horses exhibited sweating, discomfort, and periods of recumbency. As signs were more severe after SC administration this route was only used in 3/6 horses. Intravenous administration of tulathromycin was well tolerated in all horses. Mean bioavailability was 99.4% IM and 115% SC. Mean maximum plasma concentration was 645 ng/ml IM and 373 ng/ml SC. Mean half‐life was 59.8 h, 54.8 h, and 57.9 h for IV, IM, and SC administration, respectively. Mean clearance was 3.25 ml/kg/min, and mean volume of distribution was 16.8 L/kg following IV administration. Drug was detectable in plasma and BAL samples for 120 h following all routes; however, adverse effects may prevent IM use and SC use is not recommended. Tulathromycin may be a practical and affordable antimicrobial for use in adult equine patients.